ESG vs. risk management - Sekretenko, Georgii (2025)
This bachelor’s thesis examines the integration of Environmental, Social, and Governance (ESG) principles into corporate risk management within the Czech finance sector. The theoretical part reviews the evolution of ESG—from its roots in Corporate Social Responsibility to its current regulatory frameworks (e.g., CSRD, ESRS, EU Taxonomy, GRI, TCFD)—and explores key academic perspectives, including stakeholder theory, institutional theory, and the resource-based view.The study employs qualitative content analysis of 2023 non-financial reports from five leading Czech banks (Česká spořitelna, ČSOB, MONETA Money Bank, Raiffeisen Bank International, and Komerční banka), supplemented by an expert questionnaire. Analytical categories cover ESG pillars and their links to risk management, with findings synthesized across cases.Results reveal that while all banks have formal ESG strategies, the depth of integration into risk processes varies. Advanced institutions embed ESG factors into credit scoring, scenario analyses, and strategic planning, whereas others remain at a selective or developmental stage. Common barriers include data quality, methodological inconsistencies, and digitalization gaps.The thesis concludes that ESG is transitioning from compliance to a strategic resilience tool, driven by regulatory pressure and stakeholder expectations. Full internalization will require enhanced data capabilities, cross-departmental collaboration, and ongoing cultural change.